DETECTION OF B1 GENE OF TOXOPLASMA GONDII IN BLOOD OF PREGNANT AND ABORTIVE WOMEN INFECTED WITH THIS PARASITE. (Iraqi Journal of Medical Sciences, 2016)
Background: Primary maternal infection with toxoplasmosis during gestation and its transmission to the fetus continue to be the cause of tragic yet preventable disease in offspring.Objective: This study was aimed to investigate the utility of nested PCR (nPCR) technique for detection recent infection with Toxoplasma gondii in blood of pregnant and abortive women.Methods: One hundred twenty women were included in this study with a history of single or repeated abortion and thirty women with normal pregnancy were used as a control. Blood samples were tested for specific anti-Toxoplasma IgM and IgG antibodies by an enzyme-linked immunosorbent assay (ELISA) and detection of B1 gene of T. gondii by nPCR. Results: The results indicated that 43.33% of abortive women were exposed positive for anti-Toxoplasma antibodies, 4.16% of them had IgM, 25.83% had IgG, and 13.33% had both IgM and IgG, and 56.55% had no antibodies. Subsequently, nested PCR analysis was used to detecting T. gondii DNA in blood of abortive women. It was found that 15.83%of abortive women exposed positive result for B1 gene of T. gondii, those abortive women involved 10.52% of them with IgM, 31.57%with IgG, and 26.31% with both IgM and IgG, and 31.57% of them had none anti-Toxoplasma antibodies.Conclusion: It can be concluded that nPCR assay in blood has advantage in detection of recent and active toxoplasmosis.Key Words: Toxoplasma gondii, nested PCR, toxoplasmosis.
Keywords: Toxoplasma gondii; nested PCR; toxoplasmosis